Monoamniotic twins with complications and their outcome: case series - Mital, Tuhina; Rachwani, Kirti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Monoamniotic twins are identical twins sharing the same amniotic sac and placenta, with two separate umbilical cords. Although uncommon, monoamniotic twins are associated with high antenatal and perinatal morbidity and mortality. We present here a series of three cases of monoamniotic twin gestations with fetal complications who delivered in our hospital over a period of one month. Our first case Mrs. ABC with 33 weeks of gestation with Monoamniotic twins presented with twin anemia polycythemia sequence, second case, Mrs XYZ presented as primigravida with 35 weeks of gestational age with monoamniotic twins with severe preeclampsia presented with Cord entanglement who went into postpartum hemorrhage and was conservatively managed for the same. Our third case, Mrs. DEF G2P1L1 with previous scar 1.5 years back with 23 weeks of gestation with monoamniotic twins presented with Twin reversal arterial perfusion sequence and underwent medical termination of pregnancy.